Catalyst, preparation method and application thereof, and gas treatment method
By loading a catalyst with composite components on the glass fiber corrugated plate, the problems of low CO and NO conversion efficiency and short service life in the existing technology are solved, and high-efficiency conversion and long-life catalytic effects are achieved.
Patent Information
- Application Number
- CN202411343374.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-21
AI Technical Summary
When existing catalysts treat CO and NO in industrial flue gas, their conversion efficiency is low and their service life is short under sulfur-containing and high humidity conditions.
A glass fiber corrugated plate is used as a carrier, and the loaded composite components include titanium dioxide, aluminum oxide, cobalt, molybdenum, manganese, nickel and sodium. The slurry is formed by ball milling, immersed in the glass fiber corrugated plate, dried and roasted to prepare the catalyst.
The catalyst achieves efficient conversion of CO and NO, with conversion efficiency ≥90%, extended service life under sulfur-containing and high-humidity conditions, and shedding rate ≤0.23wt%.
Smart Images

Figure BDA0005060318650000131
Abstract
Description
Technical Field
[0001] The invention relates to a catalyst and a preparation method and application thereof, and a gas treatment method. Background Art
[0002] Industrial flue gas contains a large amount of sulfur dioxide, nitrogen oxides and carbon monoxide, especially in the flue gas of thermal power, steel metallurgy, cement and other industries. Catalytic oxidation of CO technology can catalytically oxidize a large amount of CO in flue gas into CO2, while releasing a large amount of heat. This heat can be reused to help the subsequent flue gas purification steps. In this way, the flue gas back-end purification process is also extended to dust removal, desulfurization, denitrification, decarbonization and other steps, which is a lengthy process and increases the cost of flue gas purification.
[0003] CN103120964B discloses a supported catalyst, which is composed of a carrier, an active substance supported on the carrier, and a binder. The binder is one or more of polypropylene resin, polyphenolic resin, polyvinyl alcohol glue, and polyvinyl acetate. The active substance is composed of a vanadium-containing compound, a molybdenum-containing compound, a sodium-containing compound, a phosphorus-containing compound, a nickel-containing compound, A1, and A2. A1 is one or more of compounds containing Li, K, Rb, Cs, Nb, Mn, Fe, Co, and Ag, and A2 is an oxide of Er and / or an oxide of Ho. The catalyst is used for preparing maleic anhydride by oxidation of benzene.
[0004] CN103028413A discloses a method for preparing a chromium-doped catalyst for catalytic oxidation of nitrogen monoxide at room temperature and pressure, which is prepared by a deposition precipitation method, wherein 10 g of a chromium precursor is weighed and dissolved in 100 ml of deionized water, and one or a combination of nitrate, chloride, and hydroxide is added, with a doping amount of 0.5-100%, stirred at room temperature to 100°C, a precipitant is added, and after adjusting the pH to 3-10, stirred for 5-8 hours, filtered, washed, dried, and calcined to obtain a chromium-doped catalyst for catalytic oxidation of nitrogen monoxide at room temperature and pressure. CN116832802A discloses a corrugated plate glass fiber material loaded with vanadium-molybdenum-titanium low-temperature catalyst, the main components of which are a mixture of molybdenum trioxide, vanadium pentoxide, and anatase titanium dioxide. The mass percentage of each component is 87.5-94.5% anatase titanium dioxide, 3.5-7.5% molybdenum trioxide, and 1-5% vanadium pentoxide. The above catalyst is only suitable for catalytic oxidation of nitrogen oxides. Summary of the invention
[0005] In view of this, an object of the present invention is to provide a catalyst having a high conversion rate for both CO and NO. Another object of the present invention is to provide a method for preparing a catalyst, which can improve the conversion efficiency of the catalyst for CO and NO and extend the service life of the catalyst under sulfur-containing high-humidity conditions. Another object of the present invention is to provide a use of a catalyst. Another object of the present invention is to provide a method for simultaneously catalytically oxidizing CO and NO in flue gas.
[0006] In one aspect, the present invention provides a catalyst, comprising a glass fiber corrugated sheet and a composite component supported on the glass fiber corrugated sheet;
[0007] The composite component includes a second carrier, an active ingredient and an alkaline ingredient;
[0008] The second carrier comprises titanium dioxide and aluminum oxide, wherein the content of the titanium dioxide is 750 to 950 parts by weight, and the content of the aluminum oxide is 50 to 150 parts by weight;
[0009] The active ingredients include cobalt, molybdenum, manganese and nickel; the content of cobalt is 120-170 parts by weight, and the mass of cobalt is calculated as cobalt nitrate; the content of molybdenum is 20-35 parts by weight, and the mass of molybdenum is calculated as ammonium molybdate; the content of manganese is 170-220 parts by weight, and the mass of manganese is calculated as manganese acetate; the content of nickel is 35-48 parts by weight, and the mass of nickel is calculated as nickel nitrate;
[0010] The alkaline component includes sodium, the content of which is 37 to 45 parts by weight, where the mass of the sodium is calculated as sodium carbonate;
[0011] Based on the volume of the glass fiber corrugated plate, the loading rate of the composite component is 400-500 g / L; after being used for 248 hours, the shedding rate of the catalyst is ≤0.23 wt%.
[0012] According to the catalyst of the present invention, preferably, the catalyst has the function of catalyzing both CO and NO.
[0013] According to the catalyst of the present invention, preferably, the conversion efficiency of the catalyst for CO is ≥ 90%, and the conversion efficiency of the catalyst for NO is ≥ 90%.
[0014] In another aspect, the present invention provides a method for preparing a catalyst, comprising the following steps:
[0015] (1) ball-milling titanium dioxide, aluminum oxide and water to obtain a mixture; ball-milling the mixture, a cobalt precursor, a molybdenum precursor, a manganese precursor, a nickel precursor, a sodium precursor, polyethylene glycol 6000 and polyvinyl pyrrolidone to form a slurry;
[0016] Among them, the amount of cobalt precursor is 120-170 parts by weight, the amount of molybdenum precursor is 20-35 parts by weight, the amount of manganese precursor is 170-220 parts by weight, the amount of nickel precursor is 35-48 parts by weight, the amount of sodium precursor is 37-45 parts by weight, the amount of polyethylene glycol 6000 is 10-50 parts by weight, the amount of polyvinyl pyrrolidone is 40-50 parts by weight, the amount of titanium dioxide is 750-950 parts by weight, and the amount of aluminum oxide is 50-150 parts by weight;
[0017] (2) immersing the glass fiber corrugated sheet in the slurry, taking it out and blowing away the excess slurry to obtain the loaded corrugated sheet;
[0018] (3) drying the loaded corrugated board at 40-60° C. for 8-20 h, at 70-90° C. for 15-25 h, and at 100-150° C. for 8-20 h to obtain a dried corrugated board;
[0019] (4) The dried corrugated plate is calcined at 250-350° C. for 1-5 h, and then calcined at 450-550° C. for 1-5 h to obtain a catalyst.
[0020] According to the preparation method of the present invention, preferably, the amount of water used is 4000 to 10000 parts by weight, and the glass fiber corrugated board is immersed in the slurry for 20 to 40 minutes.
[0021] According to the preparation method of the present invention, preferably, the cobalt precursor is cobalt nitrate, the molybdenum precursor is ammonium molybdate, the manganese precursor is manganese acetate, the nickel precursor is nickel nitrate, and the sodium precursor is sodium carbonate.
[0022] In another aspect, the present invention provides use of the above catalyst or the catalyst prepared according to the above method in the simultaneous catalytic oxidation of CO and NO.
[0023] According to the use of the present invention, preferably, the CO and NO are present in a gaseous substance, and the concentration of CO in the gaseous substance is 6000-12000 mg / Nm 3 , NO concentration is 500~800mg / Nm 3 .
[0024] According to the use of the present invention, preferably, the gaseous substance also contains O2, SO2, CO2 and water, the concentration of O2 is 10-20 vol%, and the concentration of SO2 is 15-35 mg / Nm 3 , the concentration of CO2 is 10~30vol%, and the water content is 10~25vol%.
[0025] In another aspect, the present invention provides a method for simultaneously catalytically oxidizing CO and NO in a gas, comprising the following steps:
[0026] The above catalyst or the catalyst obtained according to the above preparation method is placed in a fixed bed reactor at a space velocity of 7000 to 10000 h -1 The concentration of CO in the gas to be treated is 6000-12000 mg / Nm 3 , NO concentration is 500~800mg / Nm 3 .
[0027] The catalyst of the present invention has a high conversion efficiency for CO and NO in a sulfur-containing high-humidity environment. Furthermore, the catalyst of the present invention uses a glass fiber corrugated plate as a carrier, the catalyst is light in size, easy to operate, the catalytic reaction is sufficient, and the pollutant removal rate is high; further, the catalyst of the present invention uses non-precious metals as active components and is low in cost; further, the catalyst of the present invention uses alkaline earth metals or alkali metal elements as additives, and the catalyst has excellent sulfur resistance. DETAILED DESCRIPTION
[0028] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0029] <Catalyst>
[0030] The catalyst of the present invention comprises a glass fiber corrugated plate and a composite component supported on the glass fiber corrugated plate. In certain embodiments, the catalyst consists of a glass fiber corrugated plate and a composite component supported on the glass fiber corrugated plate. The composite component of the present invention comprises a second carrier, an active ingredient and an alkaline component. The composite component of the present invention does not include a noble metal. Examples of noble metals include, but are not limited to, gold, silver, ruthenium, rhodium, palladium, osmium, iridium, and platinum.
[0031] The second carrier includes titanium dioxide and aluminum oxide. In some embodiments, the second carrier is composed of titanium dioxide and aluminum oxide. The content of titanium dioxide is 750 to 950 parts by weight; preferably 800 to 900 parts by weight. The content of aluminum oxide is 50 to 150 parts by weight; preferably 100 to 120 parts by weight.
[0032] The active ingredients of the present invention include cobalt, molybdenum, manganese and nickel. In some embodiments, the active ingredients are composed of cobalt, molybdenum, manganese and nickel. The active ingredients composed in this way help the catalyst to have both high CO conversion efficiency and NO conversion efficiency, thereby increasing the service life of the catalyst.
[0033] Cobalt can be loaded on the glass fiber corrugated board in the form of its oxide. The content of cobalt is 120 to 170 parts by weight; preferably 130 to 160 parts by weight; more preferably 140 to 150 parts by weight. According to one embodiment of the present invention, the content of cobalt is 142.6 parts by weight. The mass of cobalt is calculated as cobalt nitrate.
[0034] Molybdenum can be loaded on the glass fiber corrugated board in the form of its oxide. The content of molybdenum is 20 to 35 parts by weight; preferably 25 to 32 parts by weight; more preferably 28 to 30 parts by weight. According to one embodiment of the present invention, the content of molybdenum is 28.8 parts by weight. The mass of molybdenum is calculated as ammonium molybdate.
[0035] Manganese can be loaded on the glass fiber corrugated board in the form of its oxide. The content of manganese is 170 to 220 parts by weight; preferably 180 to 210 parts by weight; more preferably 190 to 200 parts by weight. According to one embodiment of the present invention, the content of manganese is 197.1 parts by weight. The mass of manganese is calculated as manganese acetate.
[0036] Nickel can be loaded on the glass fiber corrugated board in the form of its oxide. The content of nickel is 35 to 48 parts by weight; preferably 37 to 45 parts by weight; more preferably 40 to 43 parts by weight. According to one embodiment of the present invention, the content of nickel is 42.8 parts by weight. The mass of nickel is calculated as nickel nitrate.
[0037] The alkaline component includes sodium. Preferably, the alkaline component is sodium. Sodium can be loaded on the glass fiber corrugated board in the form of its oxide. The content of sodium is 37 to 45 parts by weight; preferably 39 to 43 parts by weight; more preferably 40 to 42 parts by weight. According to one embodiment of the present invention, the content of sodium is 41.1 parts by weight. The mass of sodium is calculated as sodium carbonate.
[0038] Controlling the content of the composite component within the above range helps the catalyst to have both high CO conversion efficiency and NO conversion efficiency, thereby increasing the service life of the catalyst.
[0039] Based on the volume of the glass fiber corrugated plate, the loading rate of the composite component is 400-450 g / L, preferably 440-445 g / L, which helps the catalyst to have both high CO conversion efficiency and NO conversion efficiency.
[0040] After the catalyst of the present invention is used for 248 hours, the shedding rate is ≤0.23wt%; preferably, the shedding rate is ≤0.22wt%.
[0041] The catalyst of the present invention has both high CO conversion efficiency and NO conversion efficiency. The catalyst has a CO conversion efficiency of ≥90%; preferably, the CO conversion efficiency is ≥95%. The catalyst has a NO conversion efficiency of ≥90%; preferably, the NO conversion efficiency is ≥92%.
[0042] <Method for preparing catalyst>
[0043] The method for preparing the catalyst of the present invention comprises the following steps: (1) forming a slurry; (2) loading; (3) drying; and (4) calcining.
[0044] Slurry Formation Steps
[0045] Titanium dioxide, aluminum oxide and water are ball-milled to obtain a mixture; the mixture, a cobalt precursor, a molybdenum precursor, a manganese precursor, a nickel precursor, a sodium precursor, polyethylene glycol 6000, and polyvinyl pyrrolidone are ball-milled to form a slurry.
[0046] The amount of the cobalt precursor is 120 to 170 parts by weight, preferably 130 to 160 parts by weight, and more preferably 140 to 150 parts by weight. According to one embodiment of the present invention, the amount of the cobalt precursor is 142.6 parts by weight. The cobalt precursor may be cobalt nitrate.
[0047] The amount of the molybdenum precursor is 20 to 35 parts by weight, preferably 25 to 32 parts by weight, and more preferably 28 to 30 parts by weight. According to one embodiment of the present invention, the amount of the molybdenum precursor is 28.8 parts by weight. The molybdenum precursor may be ammonium molybdate.
[0048] The amount of the manganese precursor is 170 to 220 parts by weight, preferably 180 to 210 parts by weight, and more preferably 190 to 200 parts by weight. According to one embodiment of the present invention, the amount of the manganese precursor is 197.1 parts by weight. The manganese precursor may be manganese acetate.
[0049] The amount of the nickel precursor is 35 to 48 parts by weight, preferably 37 to 45 parts by weight, and more preferably 40 to 43 parts by weight. According to one embodiment of the present invention, the amount of the nickel precursor is 42.8 parts by weight. The nickel precursor may be nickel nitrate.
[0050] The mass of the sodium precursor is 37 to 45 parts by weight, preferably 39 to 43 parts by weight, and more preferably 40 to 42 parts by weight. According to one embodiment of the present invention, the mass of the sodium precursor is 41.1 parts by weight. The sodium precursor may be sodium carbonate.
[0051] The content of titanium dioxide is 750 to 950 parts by weight, preferably 800 to 900 parts by weight.
[0052] The content of aluminum oxide is 50 to 150 parts by weight, preferably 100 to 120 parts by weight.
[0053] The amount of polyethylene glycol 6000 is 10 to 50 parts by weight, preferably 20 to 40 parts by weight, and more preferably 30 to 35 parts by weight. According to one embodiment of the present invention, the amount of polyethylene glycol 6000 is 30.2 parts by weight. This can improve the conversion efficiency of the catalyst for CO and NO, and increase the service life of the catalyst.
[0054] The amount of polyvinyl pyrrolidone used is 40 to 50 parts by weight, preferably 42 to 48 parts by weight, and more preferably 44 to 47 parts by weight. According to one embodiment of the present invention, the amount of polyvinyl pyrrolidone used is 45.2 parts by weight.
[0055] The amount of water used is 4000 to 10000 parts by weight, preferably 4500 to 9000 parts by weight, and more preferably 7500 to 8550 parts by weight. According to one embodiment of the present invention, the amount of water used is 8500 parts by weight. This can maintain a proper loading rate, improve the conversion efficiency of the catalyst to CO and NO, and reduce the shedding rate.
[0056] Load Steps
[0057] The glass fiber corrugated sheet is immersed in the slurry, taken out and the excess slurry is blown off to obtain the loaded corrugated sheet.
[0058] The immersion time of the glass fiber corrugated board in the slurry is 20 to 40 minutes, preferably 25 to 35 minutes.
[0059] Drying steps
[0060] The loaded corrugated board is dried at 40-60° C. for 8-20 hours, at 70-90° C. for 15-25 hours, and at 100-150° C. for 8-20 hours to obtain a dried corrugated board.
[0061] The primary drying temperature is 40 to 60°C, preferably 45 to 55°C.
[0062] The primary drying time is 8 to 20 hours, preferably 15 to 18 hours.
[0063] The secondary drying temperature is 70-90°C, preferably 75-85°C.
[0064] The secondary drying time is 15 to 25 hours, preferably 18 to 22 hours.
[0065] The tertiary drying temperature is 100 to 150°C, preferably 120 to 135°C, and more preferably 120 to 130°C.
[0066] The drying time for the third time is 8 to 20 hours, preferably 12 to 18 hours.
[0067] The moisture content of the corrugated board after drying is less than 3wt%.
[0068] Roasting steps
[0069] The dried corrugated plate is calcined at 250-350°C for 1-5 hours, and then calcined at 450-550°C for 1-5 hours to obtain a CO catalyst. The calcination can be carried out in a muffle furnace.
[0070] The primary calcination temperature is 250-350°C, preferably 290-320°C.
[0071] The primary calcination time is 1 to 5 hours, preferably 2 to 3 hours.
[0072] The secondary calcination temperature is 450-550°C, preferably 480-520°C.
[0073] The secondary roasting time is 1 to 5 hours, preferably 3 to 4 hours.
[0074] <Use of Catalyst>
[0075] The catalyst of the present invention has a high catalytic oxidation efficiency for both CO and NO. Therefore, the present invention provides the use of the above catalyst in the simultaneous catalysis of CO and NO. CO and NO exist in gaseous substances. The concentration of CO in the gaseous substances is 6000-12000 mg / Nm 3 ; preferably 7000~11000mg / Nm 3 More preferably, 8000 to 10000 mg / Nm 3 The concentration of NO is 500~800mg / Nm 3 ; preferably 550~700mg / Nm 3 More preferably, 600 to 650 mg / Nm 3 .
[0076] The gaseous substance may also contain O2, SO2, CO2 and water. The concentration of O2 is 10-20 vol%, preferably 15-20 vol%, and more preferably 16-18 vol%. The concentration of SO2 is 15-35 mg / Nm 3 ; preferably 25 to 35 mg / Nm 3 More preferably, 28 to 35 mg / Nm 3 The concentration of CO2 may be 10 to 30 vol%, preferably 12 to 25 vol%, and more preferably 15 to 20 vol%. The content of water may be 10 to 25 vol%, preferably 15 to 20 vol%, and more preferably 16 to 18 vol%.
[0077] The catalyst can be used at a temperature of 120 to 350° C. According to one embodiment of the present invention, the catalyst is used at a temperature of 250° C.
[0078] <Gas treatment method>
[0079] The method for simultaneously catalytically oxidizing CO and NO in gas of the present invention comprises the following steps: contacting the above catalyst or the catalyst prepared according to the above method with the gas to be treated in a fixed bed reactor. The composition of the gas to be treated is as described above and will not be repeated here.
[0080] Airspeed: 5000~15000h -1 ; preferably 7500~9000h -1 More preferably 8000 to 8500 hours -1 .
[0081] The catalyst and the gas to be treated are in contact at a temperature of 120-350°C; preferably 200-300°C. According to one embodiment of the present invention, the catalyst and the gas to be treated are in contact at 250°C.
[0082] The catalyst may be used for ≥168 h; preferably, the catalyst is used for ≥200 h; more preferably, the catalyst is used for ≥240 h.
[0083] Here is the test method:
[0084] The conversion efficiency of CO and NO is as follows: The catalyst is placed in a fixed bed reactor and the catalyst and the treated gas are heated at a temperature of 250°C and a space velocity of 8000 h -1 The concentration of O2 in the gas to be treated is 16 vol%, and the concentration of CO is 8000 mg / Nm 3 , the concentration of SO2 is 35mg / Nm 3 , the concentration of NO is 600mg / Nm 3 , the concentration of CO2 is 15vol%, and the concentration of water is 16vol%.
[0085] The industrial flue gas analyzer produced by Germany's MRU company was used to test the concentrations of CO and NO at the outlet and inlet.
[0086] The CO conversion efficiency is calculated using the following formula:
[0087] CO 转化效率 =(C CO入口 -C CO出口 ) / C CO入口 ×100%
[0088] Among them, C CO入口 Indicates the CO content in the gas to be treated; C CO出口Indicates the CO content in the outlet gas.
[0089] The conversion efficiency of NO was calculated using the following formula:
[0090] NO 转化效率 =(C NO入口 -C NO出口 ) / C NO入口 ×100%
[0091] Among them, C NO入口 Indicates the content of NO in the gas to be treated; C NO出口 Indicates the NO content in the outlet gas.
[0092] The composite component volume loading rate (W1) is calculated according to the following formula:
[0093] W1=[(m2-m1) / m1]×q
[0094] Wherein, m1 is the weight of the glass fiber corrugated board; m2 is the weight of the catalyst, and q is the density of the glass fiber board, and the value of q is 75 g / L.
[0095] The shedding rate of the active component (W2) is calculated according to the following formula:
[0096] W2=(m3-m4) / m3×100%
[0097] Wherein, m3 is the mass of the catalyst before the CO and NO conversion efficiency tests, and m4 is the mass of the dry catalyst after the CO and NO conversion efficiency tests.
[0098] Example 1
[0099] (1) 900 g of titanium dioxide, 100 g of aluminum oxide and 8500 g of deionized water were ball-milled in a ball mill to obtain a mixture; 142.6 g of cobalt nitrate, 28.8 g of ammonium molybdate, 197.1 g of manganese acetate, 42.8 g of nickel nitrate, 41.1 g of sodium carbonate, 30.2 g of polyethylene glycol 6000 and 45.2 g of polyvinyl pyrrolidone were added to the mixture and ball-milled to obtain a slurry.
[0100] (2) Add a glass fiber corrugated board with a volume of 150 mm × 600 mm × 6 mm into the slurry, immerse the glass fiber corrugated board in the slurry, take it out after 30 minutes, and blow away the excess slurry with a blower to obtain a loaded corrugated board.
[0101] (3) Dry the loaded corrugated board at 50° C. for 12 h, at 80° C. for 20 h, and at 120° C. for 12 h to obtain a dried corrugated board. The moisture content of the dried corrugated board is less than 3 wt%.
[0102] (4) The dried corrugated plate was calcined in a muffle furnace at 300°C for 3 h and then at 500°C for 3 h to obtain a catalyst.
[0103] The conversion rate of CO and NO, test time, loading rate and shedding rate of the catalyst are shown in Table 1.
[0104] Comparative Example 1
[0105] Except that the amount of polyethylene glycol 6000 was 75.4 g, the rest was the same as in Example 1. The conversion rate of the catalyst to CO and NO, the test time, the loading rate and the shedding rate are shown in Table 1.
[0106] Comparative Example 2
[0107] Except that the amount of polyethylene glycol 6000 was 150.8 g, the rest was the same as in Example 1. The conversion rate of the catalyst to CO and NO, the test time, the loading rate and the shedding rate are shown in Table 1.
[0108] Comparative Example 3
[0109] Except step (2) as shown below, the rest is the same as in Example 1:
[0110] A glass fiber corrugated board with a volume of 150 mm×600 mm×6 mm was added into the slurry, and the glass fiber corrugated board was immersed in the slurry. After 45 minutes, the board was taken out and the excess slurry was blown away with a blower to obtain a loaded corrugated board.
[0111] The conversion rate of CO and NO, test time, loading rate and shedding rate of the catalyst are shown in Table 1.
[0112] Comparative Example 4
[0113] Except step (2) as shown below, the rest is the same as in Example 1:
[0114] A glass fiber corrugated board with a volume of 150 mm×600 mm×6 mm was added into the slurry, and the glass fiber corrugated board was immersed in the slurry. After 15 minutes, the board was taken out and the excess slurry was blown away with a blower to obtain a loaded corrugated board.
[0115] The conversion rate of CO and NO, test time, loading rate and shedding rate of the catalyst are shown in Table 1.
[0116] Comparative Example 5
[0117] Except that the amount of deionized water used was 10000 g, the rest was the same as in Example 1. The conversion rate of the catalyst to CO and NO, the test time, the loading rate and the shedding rate are shown in Table 1.
[0118] Comparative Example 6
[0119] Except that the amount of deionized water used was 7000 g, the rest was the same as in Example 1. The conversion rate of the catalyst to CO and NO, the test time, the loading rate and the shedding rate are shown in Table 1.
[0120] Table 1
[0121]
[0122] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.
Claims
1. A catalyst, characterized in that The catalyst comprises a glass fiber corrugated plate and a composite component supported on the glass fiber corrugated plate; The composite component includes a second carrier, an active ingredient and an alkaline ingredient; The second carrier comprises titanium dioxide and aluminum oxide, wherein the content of the titanium dioxide is 750 to 950 parts by weight, and the content of the aluminum oxide is 50 to 150 parts by weight; The active ingredients include cobalt, molybdenum, manganese and nickel; the content of cobalt is 120-170 parts by weight, and the mass of cobalt is calculated as cobalt nitrate; the content of molybdenum is 20-35 parts by weight, and the mass of molybdenum is calculated as ammonium molybdate; the content of manganese is 170-220 parts by weight, and the mass of manganese is calculated as manganese acetate; the content of nickel is 35-48 parts by weight, and the mass of nickel is calculated as nickel nitrate; The alkaline component includes sodium, the content of which is 37 to 45 parts by weight, where the mass of the sodium is calculated as sodium carbonate; Based on the volume of the glass fiber corrugated plate, the loading rate of the composite component is 400-450 g / L; after being used for 248 hours, the shedding rate of the catalyst is ≤0.23 wt%.
2. The catalyst according to claim 1, characterized in that The catalyst has the function of catalyzing both CO and NO.
3. The catalyst according to claim 1, characterized in that The conversion efficiency of the catalyst for CO is ≥90%, and the conversion efficiency of the catalyst for NO is ≥90%.
4. A method for preparing a catalyst, characterized in that: The steps include: (1) ball-milling titanium dioxide, aluminum oxide and water to obtain a mixture; ball-milling the mixture, a cobalt precursor, a molybdenum precursor, a manganese precursor, a nickel precursor, a sodium precursor, polyethylene glycol 6000 and polyvinyl pyrrolidone to form a slurry; Among them, the amount of cobalt precursor is 120-170 parts by weight, the amount of molybdenum precursor is 20-35 parts by weight, the amount of manganese precursor is 170-220 parts by weight, the amount of nickel precursor is 35-48 parts by weight, the amount of sodium precursor is 37-45 parts by weight, the amount of polyethylene glycol 6000 is 10-50 parts by weight, the amount of polyvinyl pyrrolidone is 40-50 parts by weight, the amount of titanium dioxide is 750-950 parts by weight, and the amount of aluminum oxide is 50-150 parts by weight; (2) immersing the glass fiber corrugated sheet in the slurry, taking it out and blowing away the excess slurry to obtain the loaded corrugated sheet; (3) drying the loaded corrugated board at 40-60° C. for 8-20 h, at 70-90° C. for 15-25 h, and at 100-150° C. for 8-20 h to obtain a dried corrugated board; (4) The dried corrugated plate is calcined at 250-350° C. for 1-5 h, and then calcined at 450-550° C. for 1-5 h to obtain a catalyst.
5. The preparation method according to claim 4, characterized in that: The amount of water used is 4000 to 10000 parts by weight, and the glass fiber corrugated board is immersed in the slurry for 20 to 40 minutes.
6. The preparation method according to claim 4, characterized in that: The cobalt precursor is cobalt nitrate, the molybdenum precursor is ammonium molybdate, the manganese precursor is manganese acetate, the nickel precursor is nickel nitrate, and the sodium precursor is sodium carbonate.
7. Use of the catalyst according to any one of claims 1 to 3 or the catalyst obtained according to the preparation method according to any one of claims 4 to 6 in the simultaneous catalysis of CO and NO.
8. The use according to claim 7, characterized in that The CO and NO exist in a gaseous substance, and the concentration of CO in the gaseous substance is 6000-12000 mg / Nm 3 , NO concentration is 500~800mg / Nm 3 .
9. The use according to claim 8, characterized in that The gaseous substance also contains O2, SO2, CO2 and water, the concentration of O2 is 10-20 vol%, and the concentration of SO2 is 15-35 mg / Nm 3 , the concentration of CO2 is 10~30vol%, and the water content is 10~25vol%.
10. A method for simultaneously catalytically oxidizing CO and NO in a gas, characterized in that: The steps include: The catalyst according to any one of claims 1 to 3 or the catalyst obtained by the preparation method according to any one of claims 4 to 6 is placed in a fixed bed reactor at a space velocity of 7000 to 10000 h -1 The concentration of CO in the gas to be treated is 6000-12000 mg / Nm 3 , NO concentration is 500~800mg / Nm 3 .
Citation Information
Patent Citations
Chromium-doped catalyst for catalytic oxidation of nitric oxide at normal temperature and pressure, as well as preparation method and application thereof
CN103028413A
Supported catalyst as well as preparation method and application thereof
CN103120964B
Preparation method of corrugated plate type glass fiber material supported vanadium-molybdenum-titanium low-temperature catalyst
CN116832802A